A STUDY OF NON-VERBAL COMMUNICATION SYMBOLIC MEANINGS REFLECTED IN BHARATANATYAM GESTURES - Lokumannage, Amila (Open University of Sri Lanka, 2021)
People communicate by using symbols like words or gestures that have a common meaning. In dance such symbols are gestures, movements, the whole system of figurative, nonverbal techniques explained in ancient treatises and discussed in this paper. Dance expression is possibly the most intricate and evolved, yet simply understood dance form, as it uses the body as a channel of communication (Chander, 2003). This phrase undoubtedly pertains to Indian dance as well, as it covers a variety of nonverbal communication skills that will be discussed later in this study. ...
Keywords: NON-VERBAL COMMUNICATION; BHARATANATYAM